RESEARCH ON THE LINKAGE OF DIGITAL MONEY MARKET: EMPIRICAL ANALYSIS BASED ON GRANGER CAUSALITY TEST AND VARIANCE DECOMPOSITION - Saci, Fateh (The journal of contemporary issues in business and government, 2024)
Based on the close price data of the main nine currency pairs in the digital money market in the period between 2018 and 2020, the linkage relationship between the nine currency pairs’ price changes has been empirically studied. The impact of BTCUSDT and ETHUSDT on the volatility of other currencies is analyzed using Pearson correlation coefficient, Granger causality test and variance decomposition. The results show that the price change of BTCUSDT is the reason for the price change of all other currencies. The fluctuation change of BTCUSDT can be explained by its own fluctuation. The fluctuation of other currencies has little contribution on the fluctuation of BTCUSDT. Among the contributions made on the overall market volatility, BTC’s impact on market volatility is higher than ETH’s impact on market volatility. XRP volatility can be explained by its own volatility, and its currency trend is quite different from that of other currencies.